Effects of child-parent relationship therapy on maternal parenting style and children's behavior problems in Tehran, Iran - Alizadeh, Shahla (2012)
There is much evidence to prove the effectiveness of some positive training on changing parenting style and children’s behavior problems. However, parenting style and children’s behavior problems and application of positive training for family have received little attention and research interest in Iran. Therefore, the current research is necessary and timely. Thus, the major purpose of this current study is to investigate the relationship between parenting style and children’s behavior problems and the effect of child-parent relationship therapy (CPRT) on parenting style of mothers and children’s externalizing and internalizing symptoms. CPRT is a positive training based on the concept of play therapy in which parents learn the basic principles for communicating with their children. This study was performed in two stages. The first part was a survey research to determine the relationship between parenting style and children’s behavior problem. Respondents consisted of 681 mothers of children in primary school who were identified through their children selected by random sampling. The second part was an experimental research with mothers of authoritarian an permissive who had children with internalizing and externalizing problems that they selected by random assignment (50 mothers in experimental and 50 in control group). Then CPRT as a training program was conducted on the experimental group for 10 sessions. Instruments for data collection included Parent Authority Questionnaire, PAQ (Buri, 1991) and children’s behavior checklist; CBCL (Achenbach, 1991) and intervention in the form of CPRT (Landreth & Bratton, 2006) were applied in the experimental stage. The results of the present study in the first stage indicated that there were significant inversely relationships between authoritative style of mothers with internalizing and externalizing behavior problems in their children. Also permissive and authoritarian style of mothers had positive significant correlation with internalizing and externalizing behavior problems in their children. In the experimental stage, the result showed that there were significant differences of permissive and authoritarian level of mothers between the pre and post experimental groups. In addition, there were significant differences of children’s internalizing and externalizing symptoms between pre and post in the experimental group. The findings of the present study highlighted significant relationships between the parenting styles of Iranian mothers in Tehran with children’s behavioral problems. Also the results demonstrated CPRT as a treatment in the experimental group was effective and led to a significant change in permissive and authoritarian maternal parenting style toward authoritative style and reflected by a decreased level at internalizing and externalizing symptoms of children. In conclusion, the mothers in the CPRT program learned to improve their understanding and attitude toward their children, and made the effort to reflect on their children’s feelings by playing with them according to CPRT’s rules. The mothers became more tolerant, had more realistic perceptions and developed feelings and sensitivity toward their children’s self-responsibility The Iranian government should organize practical programs such as workshops, training, or seminars to inform parents about CPRT‘s program. It can also consider to decrease children’s internalizing and externalizing symptoms throw modification of parenting styles in CPRT training. When a training program such as CPRT has been found to have significant effects on children’s behavior problems as a result of parenting styles, then counselors and psychologists can adopt and implement this program to reduce behavior problems in children.